2020
DOI: 10.1186/s12887-020-02219-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of MYCN related genes in pediatric neuroblastoma: a study based on TARGET and GEO datasets

Abstract: Background: Neuroblastoma patients with MYCN amplification are associated with poor prognosis. However, the prognostic relevance of MYCN associated genes in neuroblastoma is unclear. Methods: The expression profiles of MYCN associated genes were identified from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Gene Expression Omnibus (GEO) datasets. Enriched transcription factors and signaling pathways were determined using gene set enrichment analysis (GSEA). Kaplan-Meier plott… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Previously, we had shown that neuroblastoma patients with MYCN ampli cation were associated with adverse prognosis and revealed the prognostic signi cance of MYCN target genes using TARGET dataset [7]. In the present study, we further tested the prognostic effects of age at initial neuroblastoma diagnosis in TARGET dataset.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, we had shown that neuroblastoma patients with MYCN ampli cation were associated with adverse prognosis and revealed the prognostic signi cance of MYCN target genes using TARGET dataset [7]. In the present study, we further tested the prognostic effects of age at initial neuroblastoma diagnosis in TARGET dataset.…”
Section: Resultsmentioning
confidence: 81%
“…Neuroblastoma patients with MYCN ampli cation are classi ed into high risk sub-group and are correlated with adverse prognosis [4][5][6]. Moreover, neuroblastoma patients with high expression levels of MYCN target genes [7] or MYCN signature [8] are also associated with unfavorable clinical outcomes. On the contrary, neuroblastoma patients without MYCN ampli cation are classi ed into low risk sub-group and are often had better clinical outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analysis methods provide a new idea for the evaluation of the prognosis of NB patients. A number of models to predict the prognosis of NB, including MYCN-related signatures ( Wang et al, 2020 ), hypoxia gene signatures ( Fardin et al, 2010 ), and immune-based models ( Song et al, 2020 ), have been reported. A large number of studies have shown that GTs are related to cancer progression and can potentially serve as novel biomarkers ( Potapenko et al, 2010 ; Burchell et al, 2018 ; Tang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ARMC6 is the target gene of MYCN and indicates a poor prognosis for patients with neuroblastoma (NB) ( Wang et al, 2020a ). The transcription factor MYCN forms a heterodimer with the related transcription factor MAX and binds to the E-box DNA consensus sequence together to regulate the transcription of specific target genes ( Beierle et al, 2007 ), including ARMC6 ( Mathelier et al, 2014 ).…”
Section: Functional Interactions Of the Armc Subfamily In Specific Diseasesmentioning
confidence: 99%